2014
DOI: 10.1371/journal.pone.0088922
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Intermittent Seminal HIV-1 RNA Shedding in Patients with Undetectable Plasma Viral Load under Combination Antiretroviral Therapy

Abstract: It was demonstrated that combination antiretroviral therapy (cART) reduces the HIV-1 viral load (VL) in the blood and the seminal compartment. Some studies have reported that the seminal HIV-1 VL is undetectable in individuals with an undetectable blood plasma viral load (bpVL) under cART. However, some recent studies have demonstrated that seminal HIV-1 RNA may still be detected, and potentially infectious, even in the case of an undetectable bpVL. The aim of this retrospective study was to determine the dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 19 publications
(22 reference statements)
3
13
2
Order By: Relevance
“…). Seminal viral shedding of HIV may be associated with co‐infection such as cytomegalovirus , genital inflammations , differences in blood viral loads , ART regimen or duration of ART . In the current study, the undetectable seminal viral load we found after ART may be attributable to the relatively longer duration of ART, which differs from our previous study with only 6 months of ART .…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…). Seminal viral shedding of HIV may be associated with co‐infection such as cytomegalovirus , genital inflammations , differences in blood viral loads , ART regimen or duration of ART . In the current study, the undetectable seminal viral load we found after ART may be attributable to the relatively longer duration of ART, which differs from our previous study with only 6 months of ART .…”
Section: Discussioncontrasting
confidence: 92%
“…In the current study, the undetectable seminal viral load we found after ART may be attributable to the relatively longer duration of ART, which differs from our previous study with only 6 months of ART . Our result is consistent with those of previous studies for 6 months or more than 3 years of ART . Further studies are still needed to confirm our results in more patients receiving prolonged ART and over more intervals.…”
Section: Discussionsupporting
confidence: 81%
“…[9,2628] In our study, we found an absolute correlation between viral load in blood and in semen: in 100% of the men with undetectable plasma viral load on ART, it was also undetectable in semen. It should be noted that our study involved exhaustive screening of and treatment for genitourinary infections before determining the viral load in semen.…”
Section: Discussionmentioning
confidence: 66%
“…[29,30] It has been pointed intermittent that seminal shedding of HIV (RNA) in spite of suppression of HIV in blood and persistence of HIV DNA in semen should not be considered to place individuals at greater risk for HIV transmission than previously reported. [26,30] So some of the limitations we used in the early years of our program could be dropped in future.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in sub-Saharan Africa it is estimated that at least one-third of individuals who have been taking antiretrovirals for 12 months do not attain viral suppression (34). Furthermore, up to 48% of men taking effective antiretroviral therapy with undetectable viral load in blood plasma samples have detectable virus in their semen (35, 36). Semen washing may be relevant in such settings where men can access antiretroviral therapy and are highly adherent to it, but remain at risk of transmitting HIV to their partners.…”
Section: Discussionmentioning
confidence: 99%